2019
DOI: 10.1021/acs.chemrestox.9b00005
|View full text |Cite
|
Sign up to set email alerts
|

A Lysosome-Targetable Fluorescence Sensor for Ultrasensitive Detection of Hg2+in Living Cells and Real Samples

Abstract: A new lysosome-targetable fluorescence sensor, Lyso-HGP, was designed and synthesized based on 4-methyl-2,6-diformylphenol as a fluorophore. Lyso-HGP displays highly sensitive fluorescent detection of Hg 2+ in HEPES buffer solution (10 mM, DMSO 1%) of pH 7.0 at 37 °C due to the formation of highly fluorescent formyl-functionalized derivative Lyso-HGP-CHO. The sensor triggered a "turn-on" fluorescence response to Hg 2+ with a simultaneous increase of fluorescence intensity by 180-fold just after 10 min. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Comparatively, fluorescence sensing technologies have attracted increasing attention due to their rapid response, excellent sensitivity, high specificity, and real-time monitoring. Moreover, compared with other conventional techniques, the cost of fluorescence sensing technologies is low because they can detect specific or multiple species without resorting to expensive test equipment, complicated sample pretreatment, and strict detection condition. Over the past few decades, a great deal of fluorescent probes has been exploited for determining Hg 2+ in biological and environmental systems, and these Hg 2+ -responsive fluorescent probes are based on the reversible complexation or irreversible reaction. Unfortunately, many chelation-based fluorescent probes for determining Hg 2+ are reported to operate mainly through a fluorescence “turn-off” process. By contrast, the reaction-based fluorescent probes usually exhibit enhanced fluorescence signals by virtue of the strong thiophilic affinity of Hg 2+ and have drawn increasing interest in recent years. As a result, an increasing number of fluorescent probes have been explored for sensing Hg 2+ by employing various types of Hg 2+ receptors including thione, thionocarbonate, thiourea, and thioacetal. However, most of these reported Hg 2+ -specific probes only work well in organic solvent or organic solvent–water mixture, which severely restricts their utilization for monitoring and imaging Hg 2+ in living systems. As a consequence, it is in dire need to develop novel and efficient fluorescent probes for detecting Hg 2+ in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, fluorescence sensing technologies have attracted increasing attention due to their rapid response, excellent sensitivity, high specificity, and real-time monitoring. Moreover, compared with other conventional techniques, the cost of fluorescence sensing technologies is low because they can detect specific or multiple species without resorting to expensive test equipment, complicated sample pretreatment, and strict detection condition. Over the past few decades, a great deal of fluorescent probes has been exploited for determining Hg 2+ in biological and environmental systems, and these Hg 2+ -responsive fluorescent probes are based on the reversible complexation or irreversible reaction. Unfortunately, many chelation-based fluorescent probes for determining Hg 2+ are reported to operate mainly through a fluorescence “turn-off” process. By contrast, the reaction-based fluorescent probes usually exhibit enhanced fluorescence signals by virtue of the strong thiophilic affinity of Hg 2+ and have drawn increasing interest in recent years. As a result, an increasing number of fluorescent probes have been explored for sensing Hg 2+ by employing various types of Hg 2+ receptors including thione, thionocarbonate, thiourea, and thioacetal. However, most of these reported Hg 2+ -specific probes only work well in organic solvent or organic solvent–water mixture, which severely restricts their utilization for monitoring and imaging Hg 2+ in living systems. As a consequence, it is in dire need to develop novel and efficient fluorescent probes for detecting Hg 2+ in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…4-Mpy can adsorb onto the Au surface through its thiol group, N atoms, or π electrons and can interact with Hg 2+ and Ag + through its pyridyl group. , We will show that upon coordination with metal ions, the orientation of the 4-Mpy molecules adsorbed on AuNPs changes from nominally flat to perpendicular (Scheme B), modifying the intensity ratio of the SERS signal and enabling the quantitative determination of Hg and Ag ions in aqueous solution. This addresses an important challenge, considering that fluorescent probes for the detection of metal ions in cells require cell membrane permeability or even functionalization for specific targets located at different subcellular structures. In contrast, our nanosensors enable detection at the single-cell level due to their advantages for intracellular studies, thanks to their sub-micron size that minimizes cell damage and provides high spatial resolution and improved SERS sensitivity related to a lens effect. As a proof of concept, we will demonstrate the use of SERS-active nanofibers decorated with 4-Mpy-modified AuNPs for the detection of Hg ions in the nucleus and cytoplasm of living breast cancer cells (MCF-7).…”
mentioning
confidence: 99%
“…35 Highly selective and fast visual response of the detection of mercury ions and its application in buffer-free real water samples 36 are well-documented. Application on bioimaging and paper strips with a phenothiazine probe for the detection of mercury ions 37 and lysosome-targetable fluorescent sensor with highly selective Hg 2+ in environmental water samples and bioimaging 38 have been reported. The cyclization between phenol and acetylene to form benzofuranyl mercury chloride was discussed by Dong-Gyu Cho et al 39 Keun-Hyeung Lee et al reported enhanced fluorescence of a sensor based on an amino acid for Pb 2+ and Hg 2+ detection in an aqueous medium.…”
Section: Introductionmentioning
confidence: 99%